Answer:
y + 1 = -
(x + 4)
Explanation:
The equation of a line in point- slope form is
y - y₁ = m(x - x₁)
where m is the slope and (x₁, y₁) a point on the line
Calculate m using the slope formula
m =
![(y_(2)-y_(1) )/(x_(2)-x_(1) )](https://img.qammunity.org/2021/formulas/mathematics/middle-school/89lni2arad82a9125nchkq0vkwnbj1bzli.png)
with (x₁, y₁ ) = (- 4, - 1) and (x₂, y₂ ) = (3, - 3)
m =
=
= -
![(2)/(7)](https://img.qammunity.org/2021/formulas/mathematics/college/whmts5ovrqa5jpj8t5j7w86tgbzyeuo6b8.png)
and (x₁, y₁ ) = (- 4, - 1), then
y - (- 1) = -
( x - (- 4) ) , that is
y + 1 = -
(x + 4) ← equation of line